(untitled) (Research, Society and Development, 2021)
In the context of the Covid-19 pandemic, with the impediment of in-person classes and the imperative of relationships via the internet, this article presents part of the results of the research “Social and environmental education – narratives from the periphery”, carried out from 2020 to 2021, in state public school in Mato Grosso, in the capital Cuiabá. The objective was to present the educommunication paradigm to the Manoel Cavalcanti Proença State School, to encourage and value the communicative productions of children and adolescents. The proposals made it possible to share knowledge and connect knowledge between those who could be part of the process. Among the challenges pointed out is the digital exclusion of the majority of those enrolled who are on the margins of classes in the virtual format. The methodology was the case study, as it is a new phenomenon in that teaching unit. By proposing initiatives that unite education with communication, the research added successful results with the critical and reflective participation of students on the challenging reality, with educommunicative murals, and environmental changes with the photo and video workshop, which extended to the exhibition of the photo clothesline at the school. Despite the difficulties with limited access to the internet signal and the impediment of face-to-face interactions, the research was able to show that it is possible to make connections between people, with educommunicative actions in a school on the outskirts of Cuiabá-MT.